(Un)tolerated neighbour: encounters with the tolerated other in the reluctant fundamentalist and the submission - Seval, Ayşem (Ariel Univ Calgary, Dept English, Ss 1148 2500 Universıty Dr Nw, Calgary, Alberta T2N 1N4, Canada, 2017)
The rapidity with which discourses on respect for otherness were replaced after 9/11 almost on a global scale by those that come close to fascism puts the validity of the idea of liberal tolerance in question. As the image of the Other is defined in increasingly radicalized terms, it becomes equally difficult for the subject, that considers its self as liberal, and the "tolerated" Other to place themselves within the shifting parameters. Mohsin Hamid's The Reluctant Fundamentalist and Amy Waldman's The Submission expose the existing problematics in the nature of liberal tolerance and the difficulty of maintaining this attitude after 9/11. In an attempt to understand the underlying implications of the disintegration of the idea of liberal tolerance, this essay uses Slavoj 2iiek's concept of the Neighbour as well as Judith Butler's ideas on grief to point out how aesthetic engagements with the world of the tolerated Other may provide a critique of the current condition. At the same time, this article seeks an alternative to the discourse of tolerance.
Keywords: tolerance; Neighbour; 9/11; Mohsin Hamid; Amy Waldman